Legal and Ethical Protection in Drug Distribution: Examining Health Efforts and Drug Supervision in Indonesia - Irawan, Bobby; Januarita, Ratna; Suminar, Sri Ratna (Intellectual Law Review (ILRE), 2023)
The National Agency of Drug and Food Control (BPOM) has regulations regarding the Good Drug Distribution Method (CDOB), which is a guideline for distributing drugs properly. Community Health Centres (Puskesmas) are one of the legitimate institutions in distributing antibiotics. However, there is misuse of antibiotic distribution from community health centres to unofficial channels. This research uses normative juridical method by using secondary data from literature study and interviews with resource persons at the community health centre. The purpose of this study is to analyse the legal protection for drug users and consumers as well as the effectiveness of the legal responsibility of pharmaceutical facilities in overcoming pharmacist malpractice. The results show that legal protection for drug users is inadequate and the legal responsibility of pharmaceutical facilities is not yet effective in overcoming pharmacist malpractice, due to the lack of regulations governing pharmacist practices and firm handling of malpractice.